Mitochondria and peroxisomes : role within cellular antiviral defense - Guedes, Mariana da Rocha Soares (2014)
The present paper presents a review and compilation of all the scientifically relevant bibliography to date, regarding the antiviral signalling pathways implicated in the cellular innate immune system in humans. Emphasizing the mitochondrial antiviral signalling adaptor (MAVS), this paper explores the special features of the signal transduction pathways and their components in two specific organelles: mitochondria and peroxisomes. These pathways, ultimately, result in the expression of interferon-stimulated genes (ISGs), which are primarily responsible for fighting against viral replication, viral particle assembly and virion release within the cell. In this paper, several proposals for further investigation are also presented, since there is still a lot to learn about the role of peroxisomes in the antiviral innate immune responses.